PENCIPTAAN IKLAN LAYANAN MASYARAKAT DENGAN TEMA BIJAK BERMEDIA SOSIAL - Putri, A.A Puspa Dewi Trisna; Puriartha, I Kadek; Payuyasa, I Nyoman (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
Public service advertisements are a form of commercial communication aimed at providing information or changing people's attitudes towards certain social issues. Public service advertisements have many relevant themes, one of which is being wise on social media. Social media is a digital platform that facilitates users to interact with each other without being limited by space and time. The use of social media provides positive impacts such as a place for creativity, a source of information and education, promotion and branding. Meanwhile, the negative impacts experienced include the spread of misinformation, cyberbullying, privacy and data security issues, psychological impacts. After understanding the background of the importance of wise use of social media in everyday life and the negative impacts it causes, several main questions emerge which are the focus of this research, namely: What is the concept of producing public service advertisements about Wisely Using Social Media and What is the production process for public service advertisements about Wisely? Social Media. To answer the questions that have been formulated, this research uses several methods, namely the creation method, the idea creation method and the production method. By applying this method, this research was successful in obtaining results which show that the concept and implementation of the production of public service advertisements "Social Media Wise" can educate the public to be more careful in using social media, including filtering information before following or sharing, respecting other people's privacy, and interact positively in the digital space. It is hoped that this advertisement will be able to encourage better behavioral changes, create a healthy social media environment in utilizing technology, support the development of an intelligent, critical and responsible society in this information era.